How dare the sun rise : memoirs of a war child - Uwiringiyimana, Sandra; Pesta, Abigail (New York, NY : Katherine Tegen Books, HarperCollinsPublishers, 2017)
Sandra Uwiringiyimana was just ten years old when she found herself with a gun pointed at her head. The rebels had come at night -- wielding weapons, torches, machetes. She watched as her mother and six-year-old sister were gunned down in a refugee camp, far from their home in the Democratic Republic of the Congo. The rebels were killing people who weren't from the same community, the same tribe. In other words, they were killing people simply for looking different. "Goodbye, life," she said to the man ready to shoot her. Remarkably, the rebel didn't pull the trigger, and Sandra escaped into the night. Thus began a new life for her and her surviving family members. With no home and no money, they struggled to stay alive. Eventually, through a United Nations refugee program, they moved to America, only to face yet another ethnic disconnect. Sandra may have crossed an ocean, but there was now a much wider divide she had to overcome. And it started with middle school in New York. In this memoir, Sandra tells the story of her survival, of finding her place in a new country, and of her hope for the future.
Ages 13 and up.
Accelerated Reader AR
Accelerated Reader
Reading Counts
English.
A Junior Library Guild selection (JLG.)
Keywords: Uwiringiyimana, Sandra -- Juvenile literature; Uwiringiyimana, Sandra; Uwiringiyimana, Sandra; Refugees -- Congo (Democratic Republic) -- Biography -- Juvenile literature; Refugees -- United States -- Biography -- Juvenile literature; Massacres -- Burundi -- Bujumbura (Province) -- Juvenile literature; Women refugees -- New York (State) -- New York -- Biography; Refugees; Massacres -- Burundi -- Bujumbura Region; YOUNG ADULT NONFICTION -- Social Topics -- Emigration & Immigration; YOUNG ADULT NONFICTION -- Social Topics -- Self-Esteem & Self-Reliance.; YOUNG ADULT NONFICTION -- Social Topics -- Violence; Refugees -- United States; Massacres -- Burundi; Refugees -- Congo (Democratic Republic); Rochester (N.Y.) -- Biography -- Juvenile literature; Rochester (N.Y.) -- Biography; Rochester (N.Y.); Autobiographies; Young adult works